FOUNDATIONS AND PRINCIPLES OF EDUCATION IN ISLAMIC STUDIES - Yuyun Yunita (Pascasarjana IAIN Metro, 2021)
This paper presents the foundations and principles of Islamic education in Islamic studies. Islamic education is a process of shaping human beings in the direction that Islam aspires, including Indonesia, which is the majority of the population who are Muslim. Indonesia with its various diversity and various potentials can improve the quality of education, but it cannot be denied that it can also be swept away in an atmosphere of diversity, often this becomes a source of conflict between people. The foundation and principles of the main fortress education that provide direction in designing and implementing that education. These principles originate both from the general trend of education in the world and from both thoughts and experiences throughout the history of educational efforts in Indonesia.